Sustainable management of mangrove forest in Indonesia: Practical and Islamic perspectives - Aznawi, Andi Aznan; Mubaraq, Alfian; Al Mustaniroh, Shofiyah Sabilah; Amir, Ahmad Aldrie; Basyuni, Mohammad (Perhimpunan Intelektual Muslim Indonesia, 2025)
A mangrove forest is an ecosystem found along tropical coastlines. Indonesia has the largest mangrove land cover in the world, so it is essential to manage them, as they can provide ecological benefits to the environment and support the welfare of coastal communities through economic and social benefits. This review aimed to explore practical and Islamic perspectives on the sustainable management of mangrove forests. Sustainable management of mangrove forests, incorporating both practical strategies and Islamic principles, can enhance their role in climate change mitigation and adaptation. The sustainable management of mangrove forests in Indonesia requires a holistic approach that integrates practical measures with ethical and religious principles. By combining scientific knowledge, community engagement, and Islamic values, it is possible to create a framework for the sustainable use and preservation of these vital ecosystems. Practically, it highlights the importance of conservation, reforestation, integrated coastal zone management, and community involvement. Islam, as a religion, provides guiding principles and systems that enable problem-solving, including the management of natural resources like mangrove forests. According to Islamic law, forests are part of public property. The state or authority must responsibly manage this public property. The wealth and benefits must be shared for the welfare of the people. On the other hand, it is unlawful to damage and exploit forest resources without careful consideration of the impacts on nature and humans. These strategies not only enhance mangrove protection for carbon storage but also bolster community resilience against climate impacts. This approach not only protects the environment but also enhances the well-being of the communities that depend on mangrove forests for their livelihoods.